Analisis Kebijakan Surat Peryataan Tanggung Jawab Mutlak (SPTJM) Perkawinan Belum Tercatat Dalam Kartu Keluarga Di Dinas Dukcapil Kota Bukittinggi - Saphietry, Sastraseni; Ajidin, Asep (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The use of the Declaration of Absolute Responsibility for Unrecorded Marriages in Family Cards (Permendagri No.109 of 2019) for couples who are married religiously but have not been registered by the state on the one hand has a positive impact because it provides legal protection for citizens. But on the other hand, the use of SPTJM actually creates problems as a consequence of the policy. This research is descriptive research with a qualitative approach. The types of data used are primary data and secondary data. The results showed that the Statement of Absolute Responsibility for unregistered marriages could not be implemented at the Bukittinggi City Dukcapil Office because the policy of Permendagri 109 of 2019 was very contrary to the Marriage Law No.1 of 1974 and other regulations and the application of the use of the Statement of Absolute Responsibility (SPTJM) affected the emergence of negative implications for residents of Bukittinggi City.